Strategi Manajemen Konvergensi Media Pada Redaksi Newsroom Diskominfosantik Kabupaten Bekasi - aziza, elza; Tresnawaty, Betty; Dulwahab, Encep (Jurusan Ilmu Komunikasi, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2020)
The purpose of this study was to determine the management of news distribution media platforms and the handling of the news content production process in the editorial office of the Discominfosantik Newsroom in Bekasi District. This study uses the theory of media convergence by Henry Jenkins which describes media convergence as having made profound changes to media companies. The method used is descriptive qualitative. The results of the study show that. Firstly, the setting of the news dissemination media platform used by the Newsroom is media convergence by using a variety of news dissemination media platforms. Secondly, the handling of the news content production process in the Newsroom is determined from projection meetings to analyze the coverage topics that will be processed into news content prior to dissemination.